A slurry composition for a thick negative electrode and its preparation method and application

By adding a modified silicone oil composition aqueous solution to the negative electrode thick electrode slurry of lithium battery, the problems of easy cracking and deterioration of flexibility are solved, the performance and production efficiency of lithium batteries are improved, and the manufacturing pass rate is achieved. and battery performance.

CN115986115BActive Publication Date: 2024-12-31EVE POWER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211659298.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-22
Publication Date
2024-12-31
Estimated Expiration
2042-12-22

AI Technical Summary

Technical Problem

During the production process of lithium battery electrodes, negative electrode coating is prone to cracking, curling and flexibility, resulting in a decrease in manufacturing pass rate and a decrease in production efficiency. Current plasticizers such as N-methylpyrrolidone are difficult to recover Yamato environmental pollution risk and cannot effectively improve slurry performance.

Method used

Add a modified silicone oil composition aqueous solution to the slurry composition composition of the negative electrode to adjust the interface tension and the affinity of the active substance with the adhesive, reduce the intermolecular force and surface tension, improve flexibility and fluidity, and improve coating Performance and high temperature drying resistance.

Benefits of technology

It effectively improves the process efficiency and performance consistency of the negative electrode sheet, reduces cracking and curling phenomena, improves the circulation and storage performance of lithium batteries, and improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004013036320000131
    Figure BDA0004013036320000131
  • Figure BDA0004013036320000141
    Figure BDA0004013036320000141
Patent Text Reader

Abstract

The present invention provides a slurry composition for a thick negative electrode, a preparation method and an application thereof. The slurry composition comprises the following components by mass percentage: 91.8%-98.9% of a negative electrode active material, 0.1%-2.2% of a dispersant, 0.5%-3% of an adhesive, 0.4%-5% of a conductive agent and 0.1%-8.5% of an aqueous solution of a modified silicone oil composition. The present invention adds an aqueous solution of a modified silicone oil composition to the slurry composition for a thick negative electrode, and the aqueous solution of the composition can effectively improve the cracking and curling of the electrode during the negative electrode coating process, thereby improving the process excellence rate of the negative electrode electrode, and further improving the consistency of the electrode performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of negative electrode materials, and in particular relates to a slurry composition for a negative thick electrode and a preparation method and application thereof. Background Art

[0002] In recent years, the new energy industry has developed rapidly. Lithium-ion batteries have been widely used in passenger cars, commercial vehicles and energy storage fields, and consumer demand in various fields has achieved rapid growth. The market has also put forward higher requirements on the energy density, low temperature performance, fast charging performance, safety and cost of lithium-ion batteries. Therefore, how to further improve the energy density, production efficiency and safety performance of battery cells, and significantly extend the service life of the battery are the key research areas of many scholars.

[0003] To achieve the above goals, researchers have adopted the following different technical solutions, such as increasing the loading amount of active materials in the slurry formula, reducing the thickness of the foil, increasing the thickness of the electrode, increasing the solid content of the battery slurry, or increasing the coating speed of the slurry, etc., all of which can achieve the purpose of the same area of ​​the current collector carrying more electrode active materials, thereby increasing the energy density of the battery and reducing production costs. However, after taking the above measures, the following problems will arise in the electrode manufacturing process: for example, cracking of the electrode coating, deterioration of the flexibility of the pole piece, or wrinkling of the curling or inner ring of the winding core pole piece, etc. The above situations will cause a significant reduction in the manufacturing qualification rate of the pole piece, the quality of the battery cell will also be reduced, and the production efficiency of the battery will decrease, causing economic losses, and the manufacturing cost will also increase accordingly.

[0004] In the manufacturing process of lithium battery pole pieces, the coating temperature of mass-produced negative electrodes is as high as over 100°C, and the coating speed is also as high as over 20m / min. However, cracking of the negative electrode coating, cracking of the electrode coating, deterioration of the flexibility of the pole piece or curling, and wrinkling of the pole piece on the inner circle of the winding core may occur.

[0005] The prior art usually uses a small amount of high-boiling-point, low-volatile organic small molecule liquid as a plasticizer to improve the above-mentioned coating defects, thereby improving the quality of the negative electrode sheet. For example, the organic small molecule liquid that can be added includes N-methylpyrrolidone or ethylene carbonate, but the disadvantage of N-methylpyrrolidone is that it is difficult to recycle, and it is easy to cause environmental pollution after discharge and is harmful to the human body; ethylene carbonate is a solid crystal at room temperature with a boiling point of 248°C. It is easy to remain in the negative electrode sheet and will seep out or be dissolved by the electrolyte later, which will have an adverse effect on the rate performance, cycle performance and storage performance of the lithium battery. In addition, the disadvantages of the above-mentioned organic small molecule liquid also include that after being added to the negative electrode slurry, it can only play a role in the coating and baking process, and cannot improve the performance of the negative electrode slurry.

[0006] Therefore, in the art, there is an urgent need to develop a negative electrode slurry that not only has good fluidity and is easy to form, but also prevents the prepared negative electrode sheet from cracking, curling, and poor flexibility after high-temperature drying. Summary of the invention

[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a slurry composition for a thick negative electrode, a preparation method thereof and an application thereof. The present invention adds a modified silicone oil composition aqueous solution to the slurry composition for a thick negative electrode, and the aqueous solution of the composition can effectively improve the cracking and curling of the electrode during the negative electrode coating process, thereby improving the process efficiency of the negative electrode, and further improving the consistency of the electrode performance.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a slurry composition for a negative thick electrode, wherein the slurry composition comprises the following components by mass percentage: 91.8%-98.9% of a negative electrode active material, 0.1%-2.2% of a dispersant, 0.5%-3% of a binder, 0.4%-5% of a conductive agent, and 0.1%-8.5% of an aqueous solution of a modified silicone oil composition.

[0010] In the present invention, the slurry composition includes the following components by mass percentage: 91.8%-98.9% of negative electrode active material (for example, 91.8%, 92.2%, 92.5%, 93%, 93.5%, 94%, 94.5%, 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, 98.9%), 0.1%-2.2% of dispersant (for example, 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1 .5%, 1.8%, 2%, 2.2%), adhesive 0.5%-3% (for example, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%), conductive agent 0.4%-5% (for example, 0.4%, 0.8%, 1.2%, 2%, 3%, 4%, 5%) and modified silicone oil composition aqueous solution 0.1%-8.5% (for example, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 8.5%).

[0011] In terms of slurry preparation, the present invention adds an aqueous solution of a modified silicone oil composition to the slurry composition of the negative thick electrode. During the homogenization process, the modified silicone oil can be used to adjust the interfacial tension, improve the affinity between the negative active substance and the binder, and reduce the intermolecular force and the surface tension of the negative active substance through dissolution and penetration, thereby increasing the flexibility and fluidity of the slurry of the negative thick electrode and facilitating the coating and molding of the slurry.

[0012] In terms of pole piece coating, during the high surface density pole piece coating process, the addition of an aqueous solution of a modified silicone oil composition can improve the kinetic process of solvent volatilization during the drying process of the slurry, improve the high temperature drying resistance of the pole piece, and reduce the uneven tension of the pole piece caused by different drying speeds in different areas, thereby improving problems such as cracking, curling, and reduced flexibility of the pole piece after high temperature drying.

[0013] Preferably, the modified silicone oil composition aqueous solution comprises the following components in mass percentage: 5%-50% (5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%) of polyether modified silicone oil, 1%-10% (1%, 2%, 5%, 7%, 10%) of dispersant, 1%-10% (1%, 2%, 5%, 7%, 10%) of wetting agent and 44%-80% (44%, 50%, 55%, 60%, 65%, 70%, 75%, 80%) of deionized water, preferably 30%-40% of polyether modified silicone oil, 5%-8% of dispersant, 5%-8% of wetting agent and 44%-60% of deionized water.

[0014] In the present invention, by adjusting the mass percentage of the above-mentioned components, the surface tension of the negative electrode active material can be effectively reduced, the coating performance can be improved, and a coating with uniform appearance can be obtained. If the mass ratio of the polyether-modified silicone oil is too low, it cannot completely wet the surface of the active material; otherwise, the modified silicone oil will not be completely dissolved in the composition.

[0015] In the present invention, by adopting the modified silicone oil composition aqueous solution of the above-mentioned specific mass ratio, the dissolution and penetration of the polyether modified silicone oil can reduce the surface tension of the negative electrode active material, thereby increasing the fluidity of the negative electrode thick electrode slurry, and is conducive to the casting molding on the surface of the current collector, and at the same time can adjust the interfacial tension and improve the affinity between the negative electrode active material and the adhesive; the dispersant can enhance the solubility of the polyether modified silicone oil in deionized water; the wetting agent is used together with the modified silicone oil composition aqueous solution to adjust the interfacial tension during the homogenization process, improve the affinity between the negative electrode active material and the adhesive, and in the coating process of the high surface density pole piece, it can improve the kinetic process of solvent volatilization of the negative electrode slurry during the drying process, improve the high temperature drying resistance of the pole piece, and reduce the uneven tension of the pole piece caused by different drying speeds in different areas, thereby improving the problems of cracking, curling and poor flexibility of the pole piece after high temperature drying.

[0016] Preferably, the modified silicone oil includes any one of polyether modified silicone oil, alkyl modified silicone oil, amino modified silicone oil, phenyl modified silicone oil, hydroxyl modified silicone oil, vinyl modified silicone oil, alkoxy modified silicone oil, cyclomethyl modified silicone oil or polymethylphenyl modified silicone oil, or a combination of at least two thereof.

[0017] Preferably, the surface tension (25°C) of the polyether-modified silicone oil is 5-25mN·m, for example, 5mN·m, 10mN·m, 15mN·m, 20mN·m, 25mN·m, etc.

[0018] In the present invention, by adjusting the specific surface tension of the polyether-modified silicone oil, the composition can fully wet the surface of the negative electrode active material, effectively reduce the surface tension of the active material, improve the negative electrode coating performance, and obtain an electrode coating with no orange peel appearance and good and uniform appearance; if the surface tension is too small, the surface tension of the active material cannot be effectively reduced, the slurry fluidity is poor, and the negative electrode coating performance is poor. Conversely, the static viscosity stability of the negative electrode slurry deteriorates and the slurry is prone to sedimentation.

[0019] Preferably, the dispersant is an organic dispersant.

[0020] Preferably, the organic dispersant includes any one or a combination of at least two of triethylhexyl phosphate, methyl amyl alcohol, sodium lauryl sulfate, cellulose derivatives, polyacrylamide, guar gum or fatty acid polyethylene glycol esters.

[0021] In the present invention, the above-mentioned organic dispersant is used, which has the advantage of enhancing the solubility of the modified silicone oil in deionized water.

[0022] Preferably, the wetting agent includes any one of methanol, ethanol, propanol, butanediol, polyethylene glycol, polypropylene glycol or polybutylene glycol, or a combination of at least two thereof.

[0023] In a second aspect, the present invention provides a method for preparing a slurry composition for a thick negative electrode according to the first aspect, the method comprising the following steps:

[0024] The negative electrode active material and the conductive agent are mixed once according to the formula amount, and then a binder, a dispersant and a solvent are added and mixed twice, and then the modified silicone oil composition aqueous solution is added and mixed three times to obtain the slurry composition of the negative thick electrode.

[0025] Preferably, the primary mixing, secondary mixing and tertiary mixing are performed under stirring.

[0026] Preferably, the viscosity of the slurry composition of the negative thick electrode is 3000-10000 mPa·s, for example, 3000 mPa·s, 4000 mPa·s, 5000 mPa·s, 6000 mPa·s, 7000 mPa·s, 8000 mPa·s, 9000 mPa·s, or 10000 mPa·s.

[0027] In the present invention, the viscosity of the slurry composition of the negative thick electrode is adjusted so that the active material in the slurry is well dispersed. If the viscosity is too low, the slurry will settle, otherwise the slurry stability will deteriorate and the surface density will be unstable during thick electrode coating.

[0028] Preferably, the solid content of the slurry composition of the negative thick electrode is 48%-66%, for example, it can be 48%, 50%, 52%, 55%, 58%, 60%, 62%, or 66%.

[0029] In the present invention, the solid content of the slurry composition of the negative thick electrode is adjusted so that the negative electrode has good drying performance. If the solid content is too low, the negative electrode will be difficult to dry, otherwise the slurry stability will deteriorate and the surface density will be unstable during the thick electrode coating.

[0030] In a third aspect, the present invention provides a negative thick electrode, wherein the negative thick electrode is prepared using the slurry composition of the negative thick electrode according to the first aspect.

[0031] In a fourth aspect, the present invention provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the negative electrode sheet is the negative thick electrode according to the third aspect.

[0032] Preferably, the thickness of the negative electrode sheet is 80-500 μm, for example, 80 μm, 90 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm, or 500 μm.

[0033] The lithium-ion battery prepared by the thick negative electrode provided by the present invention has the advantages of improving the defects of the negative electrode slurry and the electrode sheet, improving the coating quality of the thick electrode, and improving the storage and cycle performance of the battery cell. At the same time, it can increase the negative electrode coating speed by more than 50%, thereby improving the production efficiency, and uses water as a solvent, which has good compatibility with the negative electrode system and has no adverse effect on the electrochemical performance of the lithium battery.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] The present invention provides a slurry composition for a thick negative electrode, wherein an aqueous solution of a modified silicone oil composition is added, and during a homogenization process, the modified silicone oil can be used to adjust the interfacial tension, thereby improving the affinity between the negative electrode active material and the adhesive, and can be used to reduce the intermolecular force and the surface tension of the negative electrode active material through dissolution and penetration, thereby increasing the flexibility and fluidity of the slurry for the thick negative electrode, and facilitating the coating and molding of the slurry.

[0036] In terms of pole piece coating, during the high surface density pole piece coating process, the addition of an aqueous solution of a modified silicone oil composition can improve the kinetic process of solvent volatilization during the drying process of the slurry, improve the high temperature drying resistance of the pole piece, and reduce the uneven tension of the pole piece caused by different drying speeds in different areas, thereby improving problems such as cracking, curling, and reduced flexibility of the pole piece after high temperature drying. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0038] Example 1

[0039] The present embodiment provides a slurry composition for a negative thick electrode, which comprises the following components by mass percentage: 95% graphite, 1.8% sodium carboxymethyl cellulose, 2% styrene-butadiene latex, 0.8% conductive carbon black and 0.4% aqueous solution of modified silicone oil composition.

[0040] The modified silicone oil composition aqueous solution comprises the following components by mass percentage: 40% of polyether modified silicone oil with a surface tension of 15 mN·m, 5% of triethylhexyl phosphoric acid dispersant, 5% of methanol wetting agent and 50% of deionized water.

[0041] This embodiment provides a method for preparing the above-mentioned slurry composition of the negative thick electrode, which comprises the following steps:

[0042] The powder of sodium carboxymethyl cellulose is added to deionized water, stirred and mixed evenly to prepare a glue solution with a solid content of 1.5%, the graphite and conductive carbon black are mixed, and then 60% of the above glue solution is added and stirred, and then the remaining 40% of the glue solution is added and stirred and dispersed, and then the modified silicone oil composition aqueous solution is added and stirred for 60 minutes, and finally the adhesive styrene-butadiene latex is added and stirred evenly to obtain a slurry composition for a negative thick electrode with a viscosity of 6000 mPa·s and a solid content of 55%.

[0043] This embodiment also provides a negative thick electrode, and the preparation method is as follows:

[0044] The prepared slurry composition of the negative thick electrode was coated on a copper foil current collector, the thickness of the current collector copper foil was 8 μm, and then oven dried, rolled and cut into pieces to form a negative thick electrode with a thickness of 250 μm.

[0045] Example 2

[0046] The present embodiment provides a slurry composition for a negative thick electrode, which comprises the following components by mass percentage: 92% graphite, 1% sodium carboxymethyl cellulose, 1% styrene-butadiene latex, 2% conductive carbon black and 4% aqueous solution of modified silicone oil composition.

[0047] The modified silicone oil composition aqueous solution comprises the following components by mass percentage: 33% of polyether modified silicone oil with a surface tension of 12 mN·m, 6% of triethylhexyl phosphoric acid dispersant, 6% of methanol wetting agent and 55% of deionized water.

[0048] This embodiment provides a method for preparing the above-mentioned slurry composition of the negative thick electrode, which comprises the following steps:

[0049] The powder of sodium carboxymethyl cellulose is added to the solvent, stirred and mixed evenly to prepare a glue with a solid content of 1.5%, the graphite and conductive carbon black are mixed, and then 60% of the above glue is added and stirred, and the remaining 40% of the glue is added and stirred and dispersed, and then the modified silicone oil composition aqueous solution is added and stirred for 60 minutes, and finally the adhesive styrene-butadiene latex is added and stirred evenly to obtain a slurry composition for a negative thick electrode with a viscosity of 5000 mPa·s and a solid content of 53%.

[0050] This embodiment also provides a negative thick electrode, and the preparation method is as follows:

[0051] The prepared slurry composition of the negative thick electrode was coated on a copper foil current collector, the thickness of the current collector copper foil was 8 μm, and then oven dried, rolled and cut into pieces to form a negative thick electrode with a thickness of 160 μm.

[0052] Example 3

[0053] The present embodiment provides a slurry composition for a negative thick electrode, which comprises the following components by mass percentage: 91.8% graphite, 1% sodium carboxymethyl cellulose, 1% styrene-butadiene latex, 1% conductive carbon black and 5.2% aqueous solution of modified silicone oil composition.

[0054] The modified silicone oil composition aqueous solution comprises the following components by mass percentage: 38% of polyether modified silicone oil with a surface tension of 18 mN·m, 7% of triethylhexyl phosphoric acid dispersant, 7% of methanol wetting agent and 48% of deionized water.

[0055] This embodiment provides a method for preparing the above-mentioned slurry composition of the negative thick electrode, which comprises the following steps:

[0056] The powder of sodium carboxymethyl cellulose is added to the solvent, stirred and mixed evenly to prepare a glue with a solid content of 1.5%, the graphite and conductive carbon black are mixed, and then 60% of the above glue is added and stirred, and then the remaining 40% of the glue is added and stirred and dispersed, and then the modified silicone oil composition aqueous solution is added and stirred for 60 minutes, and finally the adhesive styrene-butadiene latex is added and stirred evenly to obtain a slurry composition for a negative thick electrode with a viscosity of 7000 mPa·s and a solid content of 60%.

[0057] This embodiment also provides a negative thick electrode, and the preparation method is as follows:

[0058] The prepared slurry composition of the negative thick electrode was coated on a copper foil current collector, the thickness of the current collector copper foil was 8 μm, and then oven dried, rolled and cut into pieces to form a negative thick electrode with a thickness of 320 μm.

[0059] Example 4

[0060] The present embodiment provides a slurry composition for a negative thick electrode, which comprises the following components by mass percentage: 91.8% graphite, 0.2% sodium carboxymethyl cellulose, 0.5% styrene-butadiene latex, 0.7% conductive carbon black and 6.8% aqueous solution of modified silicone oil composition.

[0061] The modified silicone oil composition aqueous solution comprises the following components by mass percentage: 15% of polyether modified silicone oil with a surface tension of 5 mN·m, 2% of triethylhexyl phosphoric acid dispersant, 3% of methanol wetting agent and 80% of deionized water.

[0062] This embodiment provides a method for preparing the above-mentioned slurry composition of the negative thick electrode, which comprises the following steps:

[0063] The powder of sodium carboxymethyl cellulose is added to the solvent, stirred and mixed evenly to prepare a glue with a solid content of 1.5%, the graphite and conductive carbon black are mixed, and then 60% of the above glue is added and stirred, and the remaining 40% of the glue is added and stirred and dispersed, and then the modified silicone oil composition aqueous solution is added and stirred for 60 minutes, and finally the adhesive styrene-butadiene latex is added and stirred evenly to obtain a slurry composition for a negative thick electrode with a viscosity of 4000 mPa·s and a solid content of 48%.

[0064] This embodiment also provides a negative thick electrode, and the preparation method is as follows:

[0065] The prepared slurry composition of the negative thick electrode was coated on a copper foil current collector, the thickness of the current collector copper foil was 8 μm, and then oven dried, rolled and cut into pieces to form a negative thick electrode with a thickness of 80 μm.

[0066] Example 5

[0067] The present embodiment provides a slurry composition for a negative thick electrode, which comprises the following components by mass percentage: 97% graphite, 0.9% sodium carboxymethyl cellulose, 1% styrene-butadiene latex, 1% conductive carbon black and 0.1% aqueous solution of modified silicone oil composition.

[0068] The modified silicone oil composition aqueous solution comprises the following components by mass percentage: 48% of polyether modified silicone oil with a surface tension of 25 mN·m, 1% of triethylhexyl phosphoric acid dispersant, 1% of methanol wetting agent and 50% of deionized water.

[0069] This embodiment provides a method for preparing the above-mentioned slurry composition of the negative thick electrode, which comprises the following steps:

[0070] The powder of sodium carboxymethyl cellulose is added to the solvent, stirred and mixed evenly to prepare a glue solution with a solid content of 1.5%, the graphite and conductive carbon black are mixed, and then 60% of the above glue solution is added and stirred, and the remaining 40% of the glue solution is added and stirred and dispersed, and then the modified silicone oil composition aqueous solution is added and stirred for 60 minutes, and finally the adhesive styrene-butadiene latex is added and stirred evenly to obtain a slurry composition for a negative thick electrode with a viscosity of 3000 mPa·s and a solid content of 58%.

[0071] This embodiment also provides a negative thick electrode, and the preparation method is as follows:

[0072] The prepared slurry composition of the negative thick electrode was coated on a copper foil current collector, the thickness of the current collector copper foil was 8 μm, and then oven dried, rolled and cut into pieces to form a negative thick electrode with a thickness of 450 μm.

[0073] Example 6

[0074] The difference between this embodiment and embodiment 1 is that the aqueous solution of the modified silicone oil composition includes the following components by mass percentage: 1% polyether modified silicone oil, 5% triethylhexyl phosphoric acid dispersant, 5% methanol wetting agent and 89% deionized water, and the rest is the same as embodiment 1.

[0075] Example 7

[0076] The difference between this embodiment and embodiment 1 is that the aqueous solution of the modified silicone oil composition includes the following components in percentage by mass: 55% of polyether modified silicone oil, 5% of triethylhexyl phosphoric acid dispersant, 5% of methanol wetting agent and 35% of deionized water, and the rest is the same as embodiment 1.

[0077] Example 8

[0078] The difference between this embodiment and embodiment 1 is that the surface tension of the polyether-modified silicone oil is 1 mN·m, and the rest is the same as embodiment 1.

[0079] Example 9

[0080] The difference between this embodiment and embodiment 1 is that the molecular weight of the polyether-modified silicone oil is 2.3477 W·m and the surface tension is 30 mN·m. The rest is the same as embodiment 1.

[0081] Example 10

[0082] The difference between this embodiment and embodiment 1 is that the viscosity of the slurry composition of the negative thick electrode is 2500 mPa·s, and the rest is the same as embodiment 1.

[0083] Embodiment 11

[0084] The difference between this embodiment and embodiment 1 is that the viscosity of the slurry composition of the negative thick electrode is 10500 mPa·s, and the rest is the same as embodiment 1.

[0085] Comparative Example 1

[0086] The difference between this comparative example and Example 1 is that no aqueous solution of modified silicone oil composition is added to the slurry composition, and the slurry composition comprises the following components by mass percentage: 95% graphite, 1.8% sodium carboxymethyl cellulose, 2% styrene-butadiene latex and 1.2% conductive carbon black, and the rest are the same as Example 1.

[0087] Comparative Example 2

[0088] The difference between this comparative example and Example 1 is that the slurry composition includes the following components in mass percentage: 79.4% graphite, 1.8% sodium carboxymethyl cellulose, 2% styrene-butadiene latex, 0.8% conductive carbon black and 16% modified silicone oil composition aqueous solution, and the rest is the same as Example 1.

[0089] Comparative Example 3

[0090] The difference between this comparative example and Example 1 is that the modified silicone oil composition aqueous solution is replaced with an equal content of methanol wetting agent, and the rest is the same as Example 1.

[0091] Application Examples 1 to 11 and Comparative Application Examples 1 to 3

[0092] The thick negative electrodes provided in Examples 1 to 11 and Comparative Examples 1 to 3 are used to prepare lithium-ion batteries, and the preparation method is as follows:

[0093] Preparation of positive electrode slurry and positive electrode sheet: Add a certain amount of binder polyvinylidene fluoride powder to N-methylpyrrolidone solvent, stir and mix evenly, and prepare a glue solution with a solid content of 8%. Add the positive electrode active material lithium iron phosphate: carbon nanotubes: conductive carbon black: polyvinylidene fluoride in a mass ratio of 97.5:0.4:0.5:1.6 to the agitator, stir well to obtain positive electrode slurry, apply the prepared slurry on the current collector, the thickness of the current collector carbon-coated aluminum foil is 16μm, and then it is dried in an oven, rolled and cut into pieces to form the positive electrode sheet used for preparing the battery;

[0094] Diaphragm: Polyethylene porous polymer film is used as the diaphragm.

[0095] Preparation of electrolyte: The electrolyte contains lithium salt, organic solvent and additives, among which LiPF 6 The concentration of lithium salt is 1 mol / L, and the organic solvent is 1 mol / L LiPF 6 / EC+DMC+EMC (v / v=1:1:1) electrolyte.

[0096] Preparation of lithium-ion batteries: Assemble the positive electrode, negative electrode, separator and electrolyte, with the separator placed between the positive and negative electrodes, then wind or stack them to obtain a bare cell, place the bare cell in an outer packaging aluminum-plastic film or aluminum shell to assemble it into a cell, inject the electrolyte into the dried cell, and go through the processes of stacking, welding, gluing, assembly, liquid injection, formation, molding, capacity division and testing to form the final soft-pack lithium-ion battery.

[0097] Test conditions

[0098] The lithium-ion batteries prepared in Application Examples 1 to 11 and Comparative Application Examples 1 to 3 were subjected to room temperature cycle and rate performance tests, respectively, and the test methods are as follows:

[0099] (1) Normal temperature cycle: at 25±2℃, leave for 10min; set the current to 1C(A), leave for 5min, and perform cycle test for 2000 cycles; if the discharge capacity is less than 80% of the rated capacity, terminate the test.

[0100] (2) Rate performance: at 25±2℃, leave for 10 min; charge the battery at 0.5C(A) constant current and constant voltage until the battery voltage reaches 3.65V, with a cut-off current of 0.05C, and leave for 10 min; change the discharge current to 0.1, 0.33, 0.5 and 1C(A), respectively, repeat step 4), and conduct a multi-rate continuous discharge test.

[0101] The test results are shown in Table 1:

[0102] Table 1

[0103]

[0104]

[0105] It can be seen from the data in Table 1 that the lithium-ion batteries prepared by the thick negative electrodes provided in Application Examples 1-5 of the present invention have good cycle stability and rate performance.

[0106] Application Examples 6-7 show that adjusting the content of polyether-modified silicone oil can provide good wetting properties for the active material; Application Examples 8-9 show that adjusting the surface tension of the polyether-modified silicone oil enables the composition to fully wet the surface of the negative electrode active material, effectively reduce the surface tension of the active material, and improve the negative electrode coating performance; Application Examples 10-11 show that the viscosity of the slurry composition for the negative thick electrode is beneficial to improving the coating performance of the slurry.

[0107] Comparative Application Example 1 is a case where no modified silicone oil composition aqueous solution is added; Comparative Application Example 2 is a case where the content of the modified silicone oil composition aqueous solution is too high; Comparative Application Example 3 is a methanol wetting agent, and the comprehensive performance of the lithium-ion battery finally prepared is poor.

[0108] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A slurry composition for a negative thick electrode, characterized in that: The slurry composition comprises the following components by mass percentage: 91.8%-98.9% of negative electrode active material, 0.1%-2.2% of dispersant, 0.5%-3% of binder, 0.4%-5% of conductive agent and 0.1%-8% of modified silicone oil composition aqueous solution; The modified silicone oil composition aqueous solution comprises the following components by mass percentage: 30%-40% of polyether modified silicone oil, 5%-8% of dispersant, 5%-8% of wetting agent and 44%-60% of deionized water; The surface tension of the polyether-modified silicone oil is 5-25 mN·m; The dispersant in the aqueous solution of the modified silicone oil composition is an organic dispersant, and the organic dispersant includes any one or a combination of at least two of triethylhexyl phosphate, methyl amyl alcohol, sodium lauryl sulfate, polyacrylamide, guar gum or fatty acid polyethylene glycol ester; The viscosity of the slurry composition of the negative thick electrode is 4000-10000 mPa·s; The thickness of the negative thick electrode is 160-320 μm.

2. The slurry composition according to claim 1, characterized in that The wetting agent includes any one of methanol, ethanol, propanol, butanediol, polyethylene glycol, polypropylene glycol or polybutylene glycol, or a combination of at least two thereof.

3. A method for preparing a slurry composition for a negative thick electrode according to claim 1 or 2, characterized in that: The method comprises the following steps: The negative electrode active material and the conductive agent are mixed once according to the formula amount, and then a binder, a dispersant and a solvent are added and mixed twice, and then the modified silicone oil composition aqueous solution is added and mixed three times to obtain the slurry composition of the negative thick electrode; The viscosity of the slurry composition of the negative thick electrode is 4000-10000 mPa·s.

4. The method according to claim 3, characterized in that The primary mixing, secondary mixing and tertiary mixing are performed under stirring.

5. The method according to claim 3, characterized in that: The solid content of the slurry composition of the negative thick electrode is 48%-66%.

6. A thick negative electrode, characterized in that: The thick negative electrode is prepared using the slurry composition for the thick negative electrode according to claim 1 or 2.

7. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, and the negative electrode sheet is the negative thick electrode according to claim 6.

8. The lithium-ion battery according to claim 7, characterized in that: The thickness of the negative electrode sheet is 160-320 μm.